A three-dimensional porous copper-lithium composite negative electrode and preparation method thereof

By using rare earth brass alloy mesh in copper-lithium composite electrode for heat treatment and controllable corrosion, combined with ion exchange technology, a three-dimensional porous copper-lithium composite negative electrode with super large specific surface area and electrochemical activity was constructed, solving the problem that existing electrodes are difficult to build complex structures and have limited cyclic performance, and achieving higher structural stability and electrochemical performance.

CN119252873BActive Publication Date: 2025-03-11SANYA INST OF OCEANOGRAPHY OCEAN UNIV OF CHINA +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411765298.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing copper-lithium composite electrodes are difficult to construct complex three-dimensional porous nanostructures, with low binding and limited circulation performance.

Method used

By using rare earth brass alloy mesh for heat treatment and controllable corrosion, combined with ion exchange technology, a porous structure is constructed and the deep nanostructure construction of lithium is realized.

Benefits of technology

The construction of a three-dimensional porous copper-lithium composite negative electrode with super large specific surface area and electrochemical activity is achieved, which improves the structural stability and cyclic performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252873B_ABST
    Figure CN119252873B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrode materials, and in particular, relates to a three-dimensional porous copper-lithium composite negative electrode and a preparation method thereof. The method comprises: 1) taking a copper-zinc alloy mesh and subjecting it to heat treatment to obtain a pretreated alloy mesh; 2) placing the pretreated alloy mesh in a non-lithium salt solution for immersion and de-alloying treatment to obtain a porous copper-based alloy mesh; 3) placing the porous copper-based alloy mesh in a lithium salt solution for treatment to obtain a pretreated porous alloy mesh; 4) placing the pretreated porous alloy mesh in a molten lithium salt for melt immersion to obtain a three-dimensional porous copper-lithium composite negative electrode. The present invention effectively forms a porous structure that is favorable for lithium deposition by a controlled corrosion method, and combines ion exchange to promote the infiltration of liquid lithium and the construction of a more complex nanostructure during solidification molding, thereby realizing the construction of a three-dimensional porous copper-lithium composite negative electrode with a large specific surface area and electrochemical activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode materials, and in particular relates to a three-dimensional porous copper-lithium composite negative electrode and a preparation method thereof. Background Art

[0002] Since its commercialization in the 1990s, lithium battery technology has become the main power source for portable electronic devices and electric vehicles. However, with the expansion of application areas, the requirements for battery performance are becoming higher and higher. In particular, with the growing demand for high initial capacity batteries in portable electronic devices and electric vehicles, traditional lithium-ion battery technology is facing the dual challenges of initial capacity and cycle stability.

[0003] The theoretical capacity of negative electrode materials (such as graphite) of traditional lithium-ion batteries is limited and cannot meet the needs of future battery development. The volume expansion and contraction of lithium ions during charging and discharging may cause rupture and failure of electrode materials. At the same time, the growth of lithium dendrites may cause battery short circuit and thermal runaway, leading to safety risks.

[0004] As an innovative electrode material, copper-lithium composite electrodes show great potential for solving these challenges. First, lithium metal has an extremely high theoretical capacity, which is several times that of existing negative electrode materials, and thus shows great development potential. Copper, as an excellent conductive material, can improve the electronic conductivity of the electrode. Secondly, the addition of copper can act as a host for lithium, reduce the impact of volume expansion, improve the structural stability of the electrode, and the copper framework helps to inhibit the growth of lithium dendrites, thereby improving the safety of the battery.

[0005] However, the current research and development of copper-lithium composite electrodes is mainly focused on the effectiveness of copper-lithium composites. The general research focus is on using nanotechnology to design copper frameworks to achieve more uniform lithium ion distribution and deposition, and further improve the affinity between copper and lithium through surface modification technology to promote uniform lithium deposition. In this process, chemical vapor deposition (CVD), physical vapor deposition (PVD), etc. are usually used to achieve uniform composites of copper and lithium.

[0006] However, although the above methods have the ability to effectively combine copper and lithium, it is actually difficult to effectively construct a complex three-dimensional nanostructured copper-lithium composite electrode. In some cases, the hydrothermal method may be used to deposit lithium to construct some specific three-dimensional nanostructured copper-lithium composite electrodes, but it is difficult to construct a more complex three-dimensional porous nanocomposite structure. In addition, the copper-lithium composite electrode constructed by the hydrothermal method is prone to introduce impurities and the copper-lithium binding stability is low, and the cycle performance during actual use is still relatively limited. For this reason, the researchers have conducted further in-depth research on how to construct a three-dimensional porous composite nanomaterial copper-lithium electrode with a larger specific surface area, more active sites, and higher structural stability. Summary of the invention

[0007] In order to solve the problems that the actual structural plasticity of existing copper-lithium composite electrodes is relatively limited, it is difficult to construct a complex three-dimensional porous composite nanostructure, the degree of copper-lithium bonding is low, and the cycle performance is relatively limited, the present invention provides a three-dimensional porous copper-lithium composite negative electrode, and a preparation method of the copper-lithium composite negative electrode.

[0008] The main purpose of the present invention is:

[0009] 1. It can effectively construct a complex three-dimensional porous copper-lithium composite anode with ultra-large specific surface area and ultra-multiple active sites;

[0010] 2. Ensure that the prepared electrode has good structural stability;

[0011] 3. Improve the electrochemical properties of copper-lithium composite electrodes, such as cycle performance.

[0012] To achieve the above objectives, the present invention adopts the following technical solutions.

[0013] A method for preparing a three-dimensional porous copper-lithium composite negative electrode,

[0014] The method comprises:

[0015] 1) taking the copper-zinc alloy mesh and performing heat treatment to obtain a pretreated alloy mesh;

[0016] 2) placing the pretreated alloy mesh in a non-lithium salt solution for immersion and dealloying treatment to obtain a porous copper-based alloy mesh;

[0017] 3) placing the porous copper-based alloy mesh in a lithium salt solution for treatment to obtain a pretreated porous alloy mesh;

[0018] 4) The pretreated porous alloy mesh is placed in molten lithium salt for melt impregnation to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0019] As a preference,

[0020] Step 1) the copper-zinc alloy mesh is a copper-zinc alloy mesh containing rare earth;

[0021] In the rare earth-containing copper-zinc alloy mesh:

[0022] The zinc content is 28-42 wt%, the rare earth content is 0.5-3 wt%, and the balance is copper and inevitable impurities.

[0023] As a preference,

[0024] In the rare earth-containing copper-zinc alloy mesh, the rare earth is cerium and / or neodymium;

[0025] The rare earth content in the rare earth-containing copper-zinc alloy mesh is 0.5-1.2 wt%;

[0026] Among the unavoidable impurities, the magnesium content is ≤0.01 wt%.

[0027] As a preference,

[0028] Step 1) The heat treatment is to remove the oxide film from the copper-zinc alloy mesh, place it in a protective atmosphere, and treat it at a constant temperature of 260-290° C. for 25-35 minutes.

[0029] As a preference,

[0030] Step 2) the cations of the salt in the non-lithium salt solution are sodium ions and / or potassium ions and / or ammonium ions, and the anions are sulfate ions and / or nitrate ions and / or carbonate ions and / or bicarbonate ions;

[0031] Step 2) The cation concentration in the non-lithium salt solution is 1.2-1.8 mol / L.

[0032] As a preference,

[0033] Step 2) During the immersion dealloying treatment, the non-lithium salt solution is heated to 65-80° C. and kept warm for 18-22 hours, and ultrasonic treatment and / or bubbling treatment are simultaneously performed within the last 30-60 minutes.

[0034] As a preference,

[0035] Step 3) the lithium salt solution is 0.15-0.60 mol / L of lithium sulfate and / or lithium carbonate and / or lithium nitrate and / or lithium acetate and / or lithium oxalate and / or lithium borate;

[0036] Step 3) The treatment is to immerse the porous copper-based alloy mesh in a lithium salt solution for 90 to 150 minutes.

[0037] As a preference,

[0038] Step 4) The melt impregnation process is to immerse the pretreated porous alloy mesh into molten lithium at 195-205° C. for 15-25 minutes, filter and cool to obtain the three-dimensional porous copper-lithium composite negative electrode.

[0039] A three-dimensional porous copper-lithium composite negative electrode.

[0040] The core of the technical solution of the present invention is to deeply penetrate the copper alloy mesh to construct a deep lithium nanostructure. To this end, the present invention first constructs a three-dimensional porous carrier based on copper that is conducive to the deposition and fixation of lithium.

[0041] To this end, the present invention adopts a three-step construction of the carrier (pre-treated alloy mesh), and simultaneously realizes the pre-growth of some lithium crystals during the carrier construction process. This pre-growth process is also the key to achieving deep nano-lithium construction.

[0042] When constructing the carrier, the present invention first selects a relatively special rare earth brass alloy mesh as a precursor and performs a certain degree of heat treatment. This is because the present invention is different from the conventional dealloying treatment, but adopts a specific "corrosion" process to replace the traditional "dealloying" process. Usually, brass can be simply and efficiently dealloyed by chemical methods to remove zinc elements, thereby obtaining a porous copper mesh with extremely high purity, which can be combined with the original three-dimensional mesh structure to form a three-dimensional porous copper mesh. However, this is actually not conducive to the direct deposition of lithium, because the lithium affinity of copper itself during the lithium deposition process is relatively limited, which leads to a relatively small fixed load of lithium and poor load stability. Therefore, the present invention adopts a different approach. In the process of dealloying, the present invention uses a specific brass alloy mesh as the object to perform targeted corrosion separation of the zinc element in the form of intergranular corrosion. However, this separation will leave some zinc residues, but the residue is low and relatively evenly distributed in the corrosion holes. This allows the present invention to use a special intergranular corrosion process to control the brass alloy mesh to further form a porous structure on the basis of the three-dimensional mesh structure, and a very small amount of zinc remains on the pore walls in the porous structure.

[0043] Zinc has excellent lithium affinity. During the lithium deposition process, it can effectively guide lithium to be deposited uniformly and greatly improve the bonding strength between lithium and the deposition sites, thus achieving more stable and effective deposition. However, if conventional CVD or PVD deposition is simply performed, it is easy to increase the unevenness of the deposition and even block the holes, which will lead to a significant decrease in the specific surface area and active sites. In this regard, the intergranular corrosion process of the present invention is as follows: Figure 1 As shown, the present invention forms stable corrosion holes through a special intergranular corrosion process between the α phase and the β phase, and due to the characteristics of intergranular corrosion, it will cause the grains to pulverize and fall off, but will also produce a certain amount of residue. For example, after the intergranular corrosion process in step 2) of the present invention is completed, a very small amount of Zn can still be detected in the actual samples, and it is these zincs that provide the basis for subsequent treatment.

[0044] like Figure 2As shown, on the basis of retaining a small amount of Zn (and still possibly forming β phase) during intergranular corrosion, the present invention realizes the dynamic exchange of Zn and Li again in a manner similar to intergranular corrosion by constructing an environmental system. Although the metallic activity of Li is stronger than that of Zn, in the electrochemical sequence, the standard electrode potential of zinc is more positive than that of lithium, which means that zinc is more likely to lose electrons than lithium. The presence of copper changes the electrode potential of zinc, making this process more likely to occur, which will cause part of the lithium to be reduced and react again to form lithium / lithium hydroxide deposited on the surface of the pore wall, thereby realizing the stable combination of Cu-Li with Zn as the transition, and this will construct nucleation points that are more conducive to the infiltration and uniform deposition of liquid molten lithium in the pore wall, and may form a complex nanostructure based on LiOH, thereby realizing the construction of a deep nanostructure.

[0045] like Figure 3 As shown, the nanostructure formed by ion exchange construction mainly exists in the form of nanosheets and nano-quantum dots, which are stably attached to the surface of the alloy mesh and the inside of the pores. Therefore, on the basis of the mesh structure, a multi-scale composite structure of two-dimensional mesh + three-dimensional pores + one-dimensional nanosheets is constructed through controllable corrosion and ion exchange. While greatly improving the specific surface area of ​​the material, it achieves stable and effective loading and fixation of lithium, and also forms more sites to facilitate the subsequent impregnation of liquid molten lithium, achieving efficient lithium loading and effectively maintaining the multi-scale composite structure of two-dimensional mesh + three-dimensional pores.

[0046] In addition, it should be noted that during the treatment process of step 2) and step 3) of the present invention, the presence of chloride ions in the salt solution needs to be strictly avoided, because chloride ions themselves have the ability to corrode and corrode alloys, which may cause the corrosion process to become more complicated and uncontrollable.

[0047] The beneficial effects of the present invention are:

[0048] The present invention effectively forms a porous structure that is favorable for lithium deposition by means of controlled corrosion, and combines ion exchange to promote the formation of a more complex nanostructure during the infiltration and solidification of liquid lithium, thereby achieving the construction of a three-dimensional porous copper-lithium composite negative electrode with a large specific surface area and electrochemical activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of the rare earth brass alloy mesh used in the present invention and a typical phase diagram of the rare earth brass alloy used in the present invention;

[0050] Figure 2 A schematic diagram of the rare earth brass alloy mesh used in the present invention after corrosion and a typical phase diagram of the rare earth brass alloy used in the present invention after controllable corrosion;

[0051] Figure 3It is a schematic diagram of the rare earth brass alloy mesh used in the present invention after corrosion and ion exchange, and a SEM characterization diagram of the rare earth brass alloy used in the present invention after controllable corrosion and ion exchange. DETAILED DESCRIPTION

[0052] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0053] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0054] Unless otherwise specified, the copper-zinc alloy mesh used in the embodiments of the present invention has a zinc content of 32.0 wt %, a neodymium content of 1.2 wt %, and the remainder being copper and unavoidable impurities. The magnesium content is characterized to be ≤0.01 wt %.

[0055] Example 1

[0056] A method for preparing a three-dimensional porous copper-lithium composite negative electrode, the method comprising:

[0057] 1) Take the copper-zinc alloy mesh and place it under vacuum conditions for heat treatment at 280 °C for 30 min to obtain a pretreated alloy mesh;

[0058] 2) The pretreated alloy mesh was placed in a 0.8 mol / L sodium sulfate solution, heated to 75 °C and kept warm for 20 h for immersion dealloying treatment, and the dealloying treatment was continuously ultrasonically treated within the last 60 min to obtain a porous copper-based alloy mesh;

[0059] 3) The porous copper-based alloy mesh was immersed in a 0.50 mol / L lithium sulfate solution for 120 min to obtain a pretreated porous alloy mesh;

[0060] 4) The pretreated porous alloy mesh was placed in a molten lithium salt at 195 °C for melt impregnation for 20 min, followed by filtration and cooling to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0061] The pre-treated porous alloy mesh obtained in step 3) of this example was characterized by SEM. The characterization results are as follows: Figure 3As shown in the SEM image, a rich pore structure is constructed on the alloy mesh fiber, and lithium and lithium compounds are partially loaded in the form of nano-quantum dots and nanosheets. The specific surface areas of the copper-zinc alloy mesh used in the original step 1), the pretreated porous alloy mesh obtained in step 3), and the three-dimensional porous copper-lithium composite negative electrode obtained in step 4 are characterized respectively. The characterization results show that the specific surface area of ​​the copper-zinc alloy mesh is about 7.693 m 2 / g, while the specific surface area of ​​the pretreated porous alloy mesh formed after controlled corrosion and ion exchange increased several times, reaching 21.316 m 2 / g, which significantly improved and optimized the specific surface area of ​​the overall composite negative electrode material. After lithium loading, the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode obtained decreased to a certain extent, about 18.713 m 2 / g, but compared with the original copper-zinc alloy mesh, the specific surface area has more than doubled, achieving a very effective improvement and optimization. At the same time, the three-dimensional porous copper-lithium composite negative electrode was characterized, and the results showed that its lithium content was about 29.1%, reaching an extremely high load level.

[0062] The electrochemical properties of the prepared three-dimensional porous copper-lithium composite negative electrode were characterized, and the characterization results are shown in the following table.

[0063]

[0064] From the above characterization results, it can be clearly seen that the three-dimensional porous copper-lithium composite negative electrode of the present invention has very good electrochemical performance, showing relatively excellent initial capacity and extremely high cycle stability. Compared with the existing copper-lithium composite electrodes, the capacity retention rate is usually less than 70% after 1000 cycles under 1.0 C conditions, because it is difficult to suppress the formation of lithium dendrites during the cycle, which will cause the electrode to produce rapid performance degradation during the cycle. The present invention realizes the effective combination of Cu-Zn-Li through controllable corrosion and ion exchange, and retains a trace amount of zinc component while increasing the specific surface area of ​​the electrode material by selectively constructing a pore structure, which makes the degree of combination of Li and Cu higher and is also conducive to suppressing the formation of lithium dendrites, so that the three-dimensional porous copper-lithium composite negative electrode has very excellent electrochemical performance.

[0065] Example 2

[0066] A method for preparing a three-dimensional porous copper-lithium composite negative electrode, the method comprising:

[0067] 1) Take the copper-zinc alloy mesh and place it under vacuum conditions for heat treatment at 280 °C for 30 min to obtain a pretreated alloy mesh;

[0068] 2) The pretreated alloy mesh was placed in a 0.9 mol / L sodium sulfate solution, heated to 75 °C and kept warm for 20 h for immersion dealloying treatment, and the dealloying treatment was continuously ultrasonically treated within the last 60 min to obtain a porous copper-based alloy mesh;

[0069] 3) The porous copper-based alloy mesh was immersed in a 0.50 mol / L lithium sulfate solution for 120 min to obtain a pretreated porous alloy mesh;

[0070] 4) The pretreated porous alloy mesh was placed in a molten lithium salt at 195 °C for melt impregnation for 20 min, followed by filtration and cooling to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0071] The specific surface areas of the copper-zinc alloy mesh used in the original step 1), the pretreated porous alloy mesh obtained in step 3), and the three-dimensional porous copper-lithium composite negative electrode obtained in step 4 were characterized respectively. The characterization results showed that the specific surface area of ​​the copper-zinc alloy mesh was about 7.672 m 2 / g, while the specific surface area of ​​the pretreated porous alloy mesh formed after controlled corrosion and ion exchange increased several times, reaching 21.613 m 2 / g, which significantly improved and optimized the specific surface area of ​​the overall composite negative electrode material. After lithium loading, the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode obtained decreased to a certain extent, which was about 19.571 m 2 / g, but compared with the original copper-zinc alloy mesh, the specific surface area has more than doubled, achieving a very effective improvement and optimization. At the same time, the three-dimensional porous copper-lithium composite negative electrode was characterized, and the results showed that its lithium content was about 27.2%, reaching an extremely high load level.

[0072] The electrochemical properties of the prepared three-dimensional porous copper-lithium composite negative electrode were characterized, and the characterization results are shown in the following table.

[0073]

[0074] Compared with Example 1, it can be clearly seen that the specific surface area of ​​the product in this example is larger, but the amount of lithium deposition is reduced. This is mainly because the corrosion degree increases after the salt concentration in the non-lithium salt solution increases, the zinc retention amount decreases, and the pore size is relatively increased, but it is relatively not conducive to the initial deposition of lithium in the ion exchange process. Therefore, it can be clearly seen that the specific surface area of ​​the product in step 3) is not significantly improved compared with Example 1, but the specific surface area of ​​the product in step 4) is significantly improved. This also shows the influence of the controllable corrosion of the present invention on the structure and performance of the electrode material. In this regard, the present invention conducted a single-factor orthogonal test on this basis, controlling the sodium sulfate concentration to 0.5 mol / L, 0.6 mol / L, 0.7 mol / L and 1.0 mol / L, respectively, and performing the same experimental preparation and the same characterization under the condition that the other parameters remain unchanged. The characterization results show that when the sodium sulfate concentration is in the range of 0.6-0.9 mol / L, a relatively good preparation effect can be maintained, and the specific surface area of ​​the final product can be effectively maintained at 18.013 m 2 / g, and the lithium content can be maintained above 26.1%. When the sodium sulfate concentration is reduced to 0.5 mol / L, the controllable corrosion effect decreases significantly, which leads to a rapid decrease in the specific surface area of ​​the prepared three-dimensional porous copper-lithium composite negative electrode to 15.079 m 2 / g, and the lithium content dropped significantly to about 22.9%. This is because it is difficult for low-concentration salt solutions to effectively achieve controllable corrosion of the copper-zinc alloy network, and the pore structure is significantly reduced and the pore size is narrowed. Although more zinc components are conducive to lithium deposition, the deposition load space is limited. When the sodium sulfate concentration reaches 1.0 mol / L, the specific surface area of ​​the prepared three-dimensional porous copper-lithium composite anode is significantly increased to 20.671 m 2 / g, but the lithium content is only about 17.3%, and the lithium loading rate has dropped significantly. This is because when the salt concentration is too high, the corrosion degree will be too large, and the retention of zinc components is very small, which is not conducive to the deposition and loading of lithium, but also leads to the formation of a richer pore structure. In addition, when the sodium sulfate concentration reaches 1.0 mol / L, the 0.5 C / 1000 cycle capacity retention rate also drops sharply to about 86.7% during the electrochemical performance characterization process, which also shows that the retention of zinc also has an important influence on improving the cycle stability of electrode materials.

[0075] Example 3

[0076] A method for preparing a three-dimensional porous copper-lithium composite negative electrode, the method comprising:

[0077] 1) Take the copper-zinc alloy mesh and place it under vacuum conditions for heat treatment at 280 °C for 30 min to obtain a pretreated alloy mesh;

[0078] 2) The pretreated alloy mesh was placed in a 0.8 mol / L sodium sulfate solution, heated to 75 °C and kept warm for 20 h for immersion dealloying treatment, and the dealloying treatment was continuously ultrasonically treated within the last 60 min to obtain a porous copper-based alloy mesh;

[0079] 3) The porous copper-based alloy mesh was immersed in a 0.30 mol / L lithium sulfate solution for 120 min to obtain a pretreated porous alloy mesh;

[0080] 4) The pretreated porous alloy mesh was placed in a molten lithium salt at 195 °C for melt impregnation for 20 min, followed by filtration and cooling to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0081] The specific surface areas of the copper-zinc alloy mesh used in the original step 1), the pretreated porous alloy mesh obtained in step 3), and the three-dimensional porous copper-lithium composite negative electrode obtained in step 4 were characterized respectively. The characterization results showed that the specific surface area of ​​the copper-zinc alloy mesh was about 7.901 m 2 / g, while the specific surface area of ​​the pretreated porous alloy mesh formed after controlled corrosion and ion exchange increased several times, reaching 21.311 m 2 / g, which significantly improved and optimized the specific surface area of ​​the overall composite negative electrode material. After lithium loading, the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode obtained decreased to a certain extent, which was about 19.522 m 2 / g, but compared with the original copper-zinc alloy mesh, the specific surface area has more than doubled, achieving a very effective improvement and optimization. At the same time, the three-dimensional porous copper-lithium composite negative electrode was characterized, and the results showed that its lithium content was about 26.5%, reaching an extremely high load level.

[0082] The electrochemical properties of the prepared three-dimensional porous copper-lithium composite negative electrode were characterized, and the characterization results are shown in the following table.

[0083]

[0084] Compared with Example 1, the specific surface area of ​​the product of step 3) of this example did not change significantly, while the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode prepared in step 4) did decrease relatively significantly. This is because although zinc is beneficial to the deposition, combination and fixation of lithium and copper, and improves stability, this stability is also reflected in the cycle capacity retention rate, but for the molten lithium immersion loading, it is obvious that the lithium active sites formed by the ion exchange process have a more significant impact. The lower concentration of lithium leads to smaller lithium active sites formed by the ion exchange process, which affects the subsequent molten lithium immersion plating.

[0085] As for the concentration of lithium salt solution, the researchers also conducted a single-factor orthogonal experiment. The concentration of lithium sulfate was controlled at 0.10 mol / L, 0.15 mol / L, 0.20 mol / L, 0.60 mol / L and 0.80 mol / L respectively, and the same three-dimensional porous copper-lithium composite negative electrode was prepared while the other parameters remained unchanged. The preparation results show that when the concentration of lithium sulfate is too low, reaching 0.10 mol / L, the ion exchange process between lithium and zinc is severely hindered, so that the actual step 4) cannot effectively achieve the lithium immersion loading. The lithium content of the obtained product is only about 16.3%, while at 0.15 mol / L, the lithium content can reach 19.1%, which greatly affects the initial capacity of the electrode material. When the lithium sulfate concentration reaches 0.80 mol / L, the ion exchange process will be too intense, and the specific surface area of ​​the product in step 3) will actually decrease. In addition, although the three-dimensional porous copper-lithium composite negative electrode of step 4) shows a better initial capacity, the cycle stability is significantly reduced, and its 1.0 C / 1000 cycle retention rate drops sharply to about 71.2%, and the actual performance also decreases significantly. Therefore, based on the current experimental results, the concentration of lithium sulfate should be controlled at about 0.15-0.60 mol / L to maintain the relatively optimal preparation effect, but relatively speaking, the optimal concentration should be 0.30-0.50 mol / L.

[0086] Example 4

[0087] A method for preparing a three-dimensional porous copper-lithium composite negative electrode, the method comprising:

[0088] 1) Take the copper-zinc alloy mesh and place it under vacuum conditions for heat treatment at 280 °C for 30 min to obtain a pretreated alloy mesh;

[0089] 2) The pretreated alloy mesh was placed in a 0.8 mol / L sodium sulfate solution, heated to 75 °C and kept warm for 20 h for immersion dealloying treatment, and the dealloying treatment was continuously ultrasonically treated within the last 60 min to obtain a porous copper-based alloy mesh;

[0090] 3) The porous copper-based alloy mesh was immersed in a 0.50 mol / L lithium sulfate solution for 120 min to obtain a pretreated porous alloy mesh;

[0091] 4) The pretreated porous alloy mesh was placed in 205 °C salt for melt impregnation for 20 min, and then filtered and cooled to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0092] The specific surface areas of the copper-zinc alloy mesh used in the original step 1), the pretreated porous alloy mesh obtained in step 3), and the three-dimensional porous copper-lithium composite negative electrode obtained in step 4 were characterized respectively. The characterization results showed that the specific surface area of ​​the copper-zinc alloy mesh was about 7.711 m 2 / g, the specific surface area of ​​the pretreated porous alloy mesh formed after controlled corrosion and ion exchange increased several times, reaching 21.297 m 2 / g, which significantly improved and optimized the specific surface area of ​​the overall composite negative electrode material. After lithium loading, the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode decreased to a certain extent, about 18.501 m 2 / g, but compared with the original copper-zinc alloy mesh, the specific surface area has more than doubled, achieving a very effective improvement and optimization. At the same time, the three-dimensional porous copper-lithium composite negative electrode was characterized, and the results showed that its lithium content was about 29.6%, reaching an extremely high load level.

[0093] The electrochemical properties of the prepared three-dimensional porous copper-lithium composite negative electrode were characterized, and the characterization results are shown in the following table.

[0094]

[0095] From the above characterization results, this example increases the temperature of molten lithium, and the intermediate products and final products of the preparation process have not changed significantly compared with Example 1. However, as the temperature of molten lithium further rises to 215 ° C, the excessively high temperature easily causes the lithium active points originally formed by ion exchange to fall off, resulting in a decrease in the actual subsequent deposition effect. Although in theory the higher the temperature and the stronger the lithium fluidity, the actual loading effect should be better, that is, the loading capacity is larger, but in fact, due to the shedding of the previously formed lithium active points, the difficulty of lithium deposition has increased instead of decreased, resulting in the actual lithium loading content falling to about 23.3%. And as the temperature further increases, this situation may be further aggravated. Therefore, for the molten lithium immersion plating process, it is also necessary to effectively control the temperature of the molten lithium.

[0096] Comparative Example 1

[0097] A method for preparing a three-dimensional porous copper-lithium composite negative electrode, the method comprising:

[0098] 1) The copper-zinc alloy mesh was placed in a 0.8 mol / L sodium sulfate solution, heated to 75 °C and kept warm for 20 h for immersion dealloying treatment. Ultrasonic treatment was continuously performed in the last 60 min of the dealloying treatment to obtain a porous copper-based alloy mesh;

[0099] 2) The porous copper-based alloy mesh was immersed in a 0.50 mol / L lithium sulfate solution for 120 min to obtain a pretreated porous alloy mesh;

[0100] 3) The pretreated porous alloy mesh was placed in a molten lithium salt at 195 °C for melt impregnation for 20 min, followed by filtration and cooling to obtain a three-dimensional porous copper-lithium composite negative electrode.

[0101] The specific surface areas of the copper-zinc alloy mesh used in the original step 1), the pretreated porous alloy mesh obtained in step 2), and the three-dimensional porous copper-lithium composite negative electrode obtained in step 3) were characterized respectively. The characterization results showed that the specific surface area of ​​the copper-zinc alloy mesh was about 7.571 m 2 / g, and the specific surface area of ​​the pretreated porous alloy mesh formed after controlled corrosion and ion exchange reached 15.311 m 2 / g, and then the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode obtained after lithium loading decreased to a certain extent, about 12.019 m 2 / g. At the same time, the three-dimensional porous copper-lithium composite anode was characterized, and the results showed that its lithium content was about 17.3%, reaching an extremely high loading level.

[0102] The electrochemical properties of the prepared three-dimensional porous copper-lithium composite negative electrode were characterized, and the characterization results are shown in the following table.

[0103]

[0104] Compared with Example 1, this example did not perform heat treatment pretreatment before controlled corrosion. In fact, the heat treatment process does not directly cause corrosion, but it will cause the alloy mesh to have a significant decrease in resistance to intergranular corrosion. It can also be seen from the above characterization results that without heat treatment pretreatment, the controlled corrosion effect is significantly weakened, resulting in poor final preparation effect.

[0105] Comparative Example 2

[0106] Based on the preparation process of Example 1, this example only adjusts the copper-zinc alloy mesh material used.

[0107] The following copper-zinc alloy meshes were used for preparation:

[0108] 1. CuZn-D201, the composition is zinc content of 32.0 wt%, the balance is copper and unavoidable impurities, and the magnesium content is ≤ 0.01 wt% according to characterization, and the specific surface area is 7.615 m 2 / g;

[0109] 2. CuZn-D202, the composition is 32.0 wt% zinc, 0.1 wt% neodymium, the balance is copper and unavoidable impurities, and the magnesium content is ≤ 0.01 wt% according to characterization, and the specific surface area is 7.733 m 2 / g;

[0110] 3. CuZn-D203, the composition is 32.0 wt% zinc, 0.5 wt% neodymium, the balance is copper and unavoidable impurities, and the magnesium content is ≤0.01 wt% according to characterization, and the specific surface area is 7.593 m 2 / g;

[0111] 4. CuZn-D204, with a zinc content of 32.0 wt%, a neodymium content of 2.0 wt%, and the balance being copper and unavoidable impurities, and a magnesium content of ≤0.01 wt% as characterized, and a specific surface area of ​​7.801 m 2 / g;

[0112] 5. CuZn-D205, the composition is 32.0 wt% zinc, 3.0 wt% neodymium, the balance is copper and unavoidable impurities, and the magnesium content is ≤0.01 wt% according to characterization, and the specific surface area is 7.581 m 2 / g;

[0113] 6. CuZn-D206, with a zinc content of 32.0 wt%, a neodymium content of 3.5 wt%, and the balance being copper and unavoidable impurities, and a magnesium content of ≤0.01 wt% according to characterization, and a specific surface area of ​​7.602 m 2 / g

[0114] 7. CuZn-D207, with a zinc content of 32.0 wt%, a cerium content of 1.2 wt%, and the remainder being copper and unavoidable impurities, and a magnesium content of ≤0.01 wt% as characterized, and a specific surface area of ​​7.666 m 2 / g;

[0115] 8. CuZn-D208, the composition is 32.0 wt% zinc, 1.2 wt% dysprosium, the balance is copper and unavoidable impurities, and the magnesium content is ≤ 0.01 wt% according to characterization, and the specific surface area is 7.502 m 2 / g;

[0116] 9. CuZn-D209, composition: zinc content is 32.0 wt%, neodymium content is 1.2 wt%, magnesium content is 0.05 wt%, the balance is copper and unavoidable impurities, specific surface area is 7.707 m 2 / g.

[0117] The above copper-zinc alloy mesh was prepared in the same manner as in Example 1, and the obtained product was characterized in the same manner, wherein typical characterization results are shown in the following table.

[0118]

[0119] The specific surface area of ​​the product in the table refers to the specific surface area of ​​the three-dimensional porous copper-lithium composite negative electrode prepared in step 4).

[0120] From the above characterization results, it can be clearly seen that the preparation effect of copper-zinc alloy containing rare earth is much better than that of copper-zinc alloy without rare earth, but the rare earth should be specific cerium or neodymium, because the current research results show that only cerium and neodymium are conducive to the deepening of the degree of controllable intergranular corrosion, and relatively effectively maintain the stability of the network structure without structural collapse. However, some rare earth components, such as dysprosium, inhibit this intergranular corrosion process, resulting in poor preparation effect. In addition, the content of rare earth components also needs to be relatively strictly controlled. As the content of effective rare earth components increases, the excessive increase in the degree of intergranular corrosion will also lead to insufficient zinc residue, resulting in a decrease in the performance of the prepared product.

Claims

1. A method for preparing a three-dimensional porous copper-lithium composite negative electrode, characterized in that: The method comprises: 1) taking the copper-zinc alloy mesh and performing heat treatment to obtain a pretreated alloy mesh; 2) placing the pretreated alloy mesh in a non-lithium salt solution for immersion and dealloying treatment to obtain a porous copper-based alloy mesh; 3) placing the porous copper-based alloy mesh in a lithium salt solution for treatment to obtain a pretreated porous alloy mesh; 4) placing the pretreated porous alloy mesh in molten lithium salt for melt impregnation to obtain a three-dimensional porous copper-lithium composite negative electrode; Step 1) the copper-zinc alloy mesh is a copper-zinc alloy mesh containing rare earth; In the rare earth-containing copper-zinc alloy mesh: The zinc content is 28-42 wt%, the rare earth content is 0.5-3 wt%, and the balance is copper and unavoidable impurities; In the rare earth-containing copper-zinc alloy mesh, the rare earth is cerium and / or neodymium; The rare earth content in the rare earth-containing copper-zinc alloy mesh is 0.5-1.2 wt%; Among the unavoidable impurities, the magnesium content is ≤0.01 wt%; Step 2) the cations of the salt in the non-lithium salt solution are sodium ions and / or potassium ions and / or ammonium ions, and the anions are sulfate ions and / or nitrate ions and / or carbonate ions and / or bicarbonate ions; Step 2) the cation concentration in the non-lithium salt solution is 1.2 to 1.8 mol / L; Step 2) During the immersion dealloying treatment, the non-lithium salt solution is heated to 65-80° C. and kept warm for 18-22 hours, and ultrasonic treatment and / or bubbling treatment are simultaneously performed within the last 30-60 minutes.

2. The method for preparing a three-dimensional porous copper-lithium composite negative electrode according to claim 1, characterized in that: Step 1) The heat treatment is to remove the oxide film from the copper-zinc alloy mesh, place it in a protective atmosphere, and treat it at a constant temperature of 260-290° C. for 25-35 minutes.

3. The method for preparing a three-dimensional porous copper-lithium composite negative electrode according to claim 1, characterized in that: Step 3) the lithium salt solution is 0.15-0.60 mol / L of lithium sulfate and / or lithium carbonate and / or lithium nitrate and / or lithium acetate and / or lithium oxalate and / or lithium borate; Step 3) The treatment is to immerse the porous copper-based alloy mesh in a lithium salt solution for 90 to 150 minutes.

4. The method for preparing a three-dimensional porous copper-lithium composite negative electrode according to claim 1, characterized in that: Step 4) The melt impregnation process is to immerse the pretreated porous alloy mesh into molten lithium at 195-205° C. for 15-25 minutes, filter and cool to obtain the three-dimensional porous copper-lithium composite negative electrode.

5. A three-dimensional porous copper-lithium composite negative electrode prepared by the method of any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparation method of composite three-dimensional metal lithium negative electrode for inhibiting growth of lithium dendrites

    CN113871585A

  • Self-propagating alloying lithium negative electrode and preparation method thereof

    CN114141992A